2015
DOI: 10.5539/gjhs.v8n1p90
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of the Emergency Department and Predicting Factors Associated With Its Use at the Saudi Ministry of Health General Hospitals

Abstract: Overuse of emergency rooms (ER) is a public health problem. To investigate this issue, a cross-sectional survey was conducted at the ERs of King Abdul-Aziz Hospital, King Fahd Hospital, and Al-Thaghor Hospital in November 2013 with the aims of estimating emergency service utilization for non-urgent cases, identifying the predictors of ER utilization for non-urgent cases, and measuring patients’ knowledge of primary healthcare centers (PHCCs). Patients were interviewed using a structured questionnaire and the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 22 publications
1
38
0
Order By: Relevance
“…Most of the non-urgent patients thought that the ED is the first place to seek for in case of sickness. 6 Jeddah city is the second largest city in Saudi Arabia and serves as an entry point for Hajj pilgrims, with a total population of 4.3 million. Total hospital beds per 10 000 population in Jeddah is 7.4 compared with 10 in Riyadh.…”
Section: Open Accessmentioning
confidence: 99%
“…Most of the non-urgent patients thought that the ED is the first place to seek for in case of sickness. 6 Jeddah city is the second largest city in Saudi Arabia and serves as an entry point for Hajj pilgrims, with a total population of 4.3 million. Total hospital beds per 10 000 population in Jeddah is 7.4 compared with 10 in Riyadh.…”
Section: Open Accessmentioning
confidence: 99%
“…Our study (Table ) found that the overall figure (33%) for ED visits with nonurgent presentation (NUP) (ESI 4‐5) was similar to the percentage (37% [range 8%‐62%]) of all ED visits in the United States that were judged to be NUP . The figures from a few LMICs such as Saudi Arabia and Iran were 20% to 72% . However, these figures were based on varying definitions across studies, hence rendering difficulty in comparison.…”
Section: Discussionmentioning
confidence: 99%
“…13 The figures from a few LMICs such as Saudi Arabia and Iran were 20% to 72%. 14,15 However, these figures were based on varying definitions across studies, hence rendering difficulty in comparison.…”
Section: Workforce Status Vis-à-vis the Workloadmentioning
confidence: 99%
“…In instances of general emergency care, where patients have genuinely sustained injuries warranting hospital attention, the assessment of a qualified paramedic is invaluable (Halter, Humphreys et al, 2017;Snooks et al, 2017). However, inappropriate use of emergency services also causes a degree of dissonance and frustration in relation to the perceptions that paramedic practitioners hold of those they potentially need to assess, diagnose and manage in the context of an emergency response (Dejean et al, 2016) whether this is related to ambulance use or treatment in hospital (Cardona-Morrell et al, 2017;Franchi et al, 2017;Dawoud et al, 2016). In the context of residential care home settings there was a high degree of ambiguity around the assessment of sustained injuries and whose responsibility this was, particularly in relation to falls where potentially non-visible injuries which were subsequently not immediately identifiable, where patients were moved via hoists.…”
Section: Discussionmentioning
confidence: 99%